LITERATURE-ART PHENOMENON: TRANSDISTSIPLINARNE DESIGN - Roudnitsky, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Loutsac S. M. Dominanta as mental oserdya of houdogno-estetichnogo process (on material of Ukrainian literature of border of XIX - XX ages). Ivano-Frankivs’k: Folio, 2010. - 400 p.